Manual de Prácticas para el Mejor Manejo Postcosecha del Mango - Jeffrey K. Brecht; Steven A. Sargent; Adel A. Kader; Elizabeth J. Mitcham; Fernando Maul; Patrick E. Brecht; Octavio Menocal (EDIS, 2011)
This 78-page Spanish-language manual includes quality-control procedures to use when monitoring the maturity and quality of mangos in commercial handling operations. It was written by Jeffrey K. Brecht, Steven A. Sargent, Adel A. Kader, Elizabeth J. Mitcham, Fernando Maul, Patrick E. Brecht, and Octavio Menocal, and published by the UF Department of Horticultural Sciences, January 2011.